1985
DOI: 10.3382/ps.0641678
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Aflatoxin on Young Turkeys and Broiler Chickens

Abstract: The effect of crude aflatoxin (AF) on the growth, performance, and immune response of turkeys and broilers was studied. Crude AF, produced from a natural outbreak of Aspergillus flavus on corn, was ground and mixed in rations to contain either 0, 100, 200, 400, or 800 ppb of aflatoxin B1 (AFB1). Turkeys (Experiment 1) and broilers (Experiment 2) were used in identical experimental designs. In each, 200, 14-day-old birds were divided equally by sex into five groups of 40 and were fed one of five AF diets for 35… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

13
47
0
5

Year Published

1994
1994
2024
2024

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 100 publications
(65 citation statements)
references
References 11 publications
13
47
0
5
Order By: Relevance
“…However, supplementing 500 or 750 ppb AFB, resulted in a poorer (P<0.05) feed conversion compared to that observed for the controls (Table 2). These data are in agreement with those published by Giambrone et al (1985b), who reported poorer feed conversion in birds fed 400 ppb AFB, in a corn-based diet. No data on feed consumption were reported in that study.…”
Section: Body Weight Feed Consumption and Feed Conversionsupporting
confidence: 83%
See 2 more Smart Citations
“…However, supplementing 500 or 750 ppb AFB, resulted in a poorer (P<0.05) feed conversion compared to that observed for the controls (Table 2). These data are in agreement with those published by Giambrone et al (1985b), who reported poorer feed conversion in birds fed 400 ppb AFB, in a corn-based diet. No data on feed consumption were reported in that study.…”
Section: Body Weight Feed Consumption and Feed Conversionsupporting
confidence: 83%
“…However, those fed 500 ppb AFB, and 750 ppb AFB, were significantly lighter (P<0.05) than the controls (Table 2). These data agree with other reports (Giambrone et al, 1985a and1985b), in which a significant reduction in body weight in five-week-old broilers was observed only when fed a diet supplemented with at least 500 ppb AFB,.…”
Section: Body Weight Feed Consumption and Feed Conversionsupporting
confidence: 82%
See 1 more Smart Citation
“…Similarly, Verma et al, (2004) reported a significant decrease in the relative weight of the bursa of Fabricius when birds were exposed to diets having 2000 ppb AF. Similar reduction in BBR and moderate histopathological changes have been reported in broilers (Giambrone et al, 1985;Marquez and Hernandez, 1995), laying hens (Dafalla et al, 1987), ducks (Sell et al, 1998;Khajarern and Khajarern, 1999) and wild turkeys (Quist et al, 2000) when birds were fed diets having various levels of AF (100 to 500 ppb). In addition, vacuolation of liver cells and cellular depletion in the follicle medulla of the bursa Fabricii has been reported to be produced as an indication of aflatoxicosis by feeding lower levels of AF (100 ppb) over a long-term period of 42 days (Espada et al, 1992).…”
Section: Bursal Body Weight Ratio (Bbr)mentioning
confidence: 48%
“…Afetam taxa de crescimento, conversão alimentar e eficiência reprodutiva do plantel, com repercussões sobre a relação custo-benefício das indústrias avícolas (Jelinek et al, 1989;Santin et al, 2001). As intoxicações, em sua maioria, são decorrentes da ingestão acidental de pequenas quantidades de xenobióticos fúngicos, resultando em declínio mensurável do desempenho produtivo e em alterações clínicas que, embora inespecíficas, estão relacionadas com a ocorrência de hemorragias subcutâneas e imunossupressão (Giambrone et al, 1985).A ocratoxina A (OTA) é um pentapeptídeo derivado da isocumarina e da L-b-fenilalanina, produzido sob a forma de metabólito secundário por várias espécies de Aspergillus e Penicillium (Pitt, 2000a;Pitt, 2000b). Sua denominação foi definida por ter sido isolada pela primeira vez, como produto xenobiótico, de cultivares de Aspergillus ochraceus (StuderKohr et al, 1995).…”
unclassified